Kecemasan Siswa Menghadapi Ujian dan Implikasinya dalam Layanan Bimbingan dan Konseling - Yulianti Karlina; Yulidar Ibrahim (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
Abstract This study aims to describe the anxiety of students facing examinations and their implications in guidance and counseling services (BK). This type of research is quantitative descriptive. The population of this study is the students of Pertiwi 1 Padang High School class X and XI in the academic year 2018-2019. The research sample amounted to 213 people. The research was carried out by administering questionnaire instruments. Data were analyzed by percentage analysis. The findings of this study indicate the results of anxiety students facing examinations at Pertiwi 1 Padang High School are in the quite anxious category, the results are in more detail (1) anxiety students face tests on cognitive aspects in the category of quite anxious, (2) anxiety students face tests on affective aspects in the category of quite anxious, (3) the anxiety of students facing the test on the somatic aspect is in the category of quite anxious, (4) the anxiety of students facing the test on aspects of behavior is in the category of quite anxious.Keyword: Anxiety Facing Exams, Guidance and Counseling Services